2018
DOI: 10.1086/696920
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality of Upper-Secondary Vocational Education and Training: Evidence from China

Abstract: An increasing number of policymakers in developing countries have made the mass expansion of upper-secondary vocational education and training (VET) a top priority. The goal of this study is to examine whether VET fulfills the objectove of building skills and abilities along multiple dimensions and further identify which school-level factors help vocational students build these skills and abilities. To fulfill this goal, we analyzed representative, longitudinal data that we collected on more than 12,000 studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…However, a large share of the rise is from VET also. Perhaps because in relative terms VET expanded even faster than AH, there is concern that learning may not be as effective as it could be (if the VET system were delivering a higher quality education in many of the schools) and that many students, while starting upper secondary schooling, are not finishing (in no small part because they do not believe they are learning—Yi et al 2015, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, a large share of the rise is from VET also. Perhaps because in relative terms VET expanded even faster than AH, there is concern that learning may not be as effective as it could be (if the VET system were delivering a higher quality education in many of the schools) and that many students, while starting upper secondary schooling, are not finishing (in no small part because they do not believe they are learning—Yi et al 2015, ).…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 48% of all Chinese students are streamed into the vocational route (Woronov 2015, 42). It has been observed that China's VET colleges have inadequately trained teaching staff (Shi 2013), poor student progression (Yi et al 2018), weak links with industry (Liang and Chen 2014;Stewart 2015), and tenuous ties with the needs of the labour market (Cooke 2012). Since the students who enrol in vocational colleges are generally those who have fared worse academically (Li 2004;Mok 2001;Yang 2004;Zha 2012;Liu and Wang 2015), they become stereotyped as 'educational failures' and 'stupid and lazy youths' (Woronov 2015), who are considered to deserve the limited occupational opportunities open to them (Woronov 2015;Ling 2015).…”
Section: Chinese Vet Vet Students and Stereotypingmentioning
confidence: 99%
“…Moreover, VUSS students have a higher tendency to drop out. 11 The primary determinant of whether a student attends an AUSS or a VUSS is that student's performance on an entrance exam. Given that uncorrected vision in primary and middle school can lead to reduced academic performance, 3,7 students without spectacles or with incorrect prescriptions may be attending VUSSs at higher rates than are consistent with their abilities.…”
Section: Introductionmentioning
confidence: 99%